Learning Force and Motion Using Problem Based Learning in Elementary School - Sunarti Sunarti; Hasanah Hasanah; Frits Womsiwor (JP2D (Jurnal Penelitian Pendidikan Dasar) UNTAN, 2022)
This study aims to improve students' knowledge and understanding of forces and motion. Each individual does not know precisely where the material will be given when starting the effective learning process that is appropriate and not difficult to improve overall abilities and knowledge through problem-based learning (PBL). The method with a quantitative descriptive research approach, Classroom Action Research (CAR), is a way of determining how to do it with cycles. The participants were 26 sixth grade students in elementary school. Cycle 1 passed 15 students with a percentage of 65%. Those who have not passed are eight students, with a percentage of 35%. Then, continued to cycle II implementing the PBL Model, 26 students passed with a percentage of 100%.